Life skills for adolescence : evaluative research on the Quest programme - Sliedrecht, Susan Beverley (Department of Social Development, 2016)
The Quest Life Skills for Adolescence is a two-year programme, for Standard 6 and 7 pupils. The goal of the programme is to assist adolescents to effectively manage the life tasks associated with the adolescent years. The programme is school based consisting of eight modules, each module dealing with a different subject. The method of instruction, as with most life skills programmes, is participatory learning as opposed to didactic teaching. This pilot-study was based at the Sentinel High School in Hout Bay. The study evaluates whether module one and two of the Quest Life Skills programme achieved their objectives. The second purpose was to devise an evaluation tool that could be used by other schools to evaluate modules one and two of the Quest programme. A multifaceted study design was adopted in the evaluation process. The instruments used were questionnaires, group discussions, Rosenberg's Self-Esteem Scale (1965) and a game. The results reveal that module one of the programme did enable pupils to gain a better understanding of adolescence. Pupils were, however, not totally conversant with the four aspects of change that would take place in adolescence namely physical, emotional, social and intellectual change. They seemed more familiar with the changes that would take place in the physical and emotional realms than in the intellectual and social realms. The findings confirmed that a safe supportive environment, conducive to learning, had been established. Module two of the programme dealt with self-confidence/self-esteem. The self-esteem of participant's, in the Quest programme, increased marginally, but the results yielded showed that a statistically significant improvement did not take place when compared with the comparative group. Participants reported that the programme was of great benefit to them. It was the first time for the majority of the participants that they had been exposed to life skills training. Based on the above findings, an evaluation package was compiled, for schools to use, to evaluate the effectiveness of the first two modules of the Quest programme.